Food detection in medieval acoustic vessels - Filip Facincani; Jaroslav Pavelka (Archeologické Rozhledy)
The subject of the article is two systems of acoustic vessels from the Church of St. Gall in Myšenec, which is associated with the production of the so-called Zvíkov and Písek architectural workshop, and All Saints Church in Kovářov in South Bohemia. These vessels, built into the vault, were placed with their rim facing the interior of the presbytery and their bottom in the space of the attic at the same time as the construction of the vault and were probably intended to improve the acoustics of the interior of the presbytery. In the foreign synthesising literature, examples are described of custom-made vessels as well as secondarily used household vessels, i.e. those primarily intended for food storage. The paper aims to precisely determine the primary role of the vessels found in the two studied churches by detecting the hypothetical presence of food residues in them. Samples were taken from the inner surfaces of the vessels and their analysis showed a weak signal of casein (milk) in one case and a strong signal of gliadin (grain) in the other. The multiple potential functions of the vessels embedded in the vaults are discussed in the context of Czech examples and foreign research on acoustic vessels.